Interview with Prof. Antonia F. Chen: please never give up as long as you love what you are doing - Yan, Crystal M. (Annals of Joint; Vol 4 (March 2019): Annals of Joint, 2019)
On Feb 28, 2019, Antonia F. Chen from Brigham and Women’s Hospital came to Nanjing to have a brief academic exchange with domestic peers on the prevention, diagnosis and treatment of periprosthetic joint infection (PJI) (Figure 1). We were honored to invite Prof. Chen, who is currently the Director of Research, Arthroplasty Service at Brigham and Women’s Hospital at Harvard Medical School, to have an interview with us, sharing her experience in the field of orthopaedic infection.